2021
DOI: 10.1016/j.ehb.2021.101048
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and food away from home: What drives the socioeconomic gradient in excess body weight?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Literature indicates that food away from home is generally less healthy and is significantly associated with a higher prevalence of obesity [ 11 , 46 ]. In the present study, most participants reported eating away from home at least once a week which is similar to findings reported previously in the UAE, the United States, and Vietnam [ 35 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Literature indicates that food away from home is generally less healthy and is significantly associated with a higher prevalence of obesity [ 11 , 46 ]. In the present study, most participants reported eating away from home at least once a week which is similar to findings reported previously in the UAE, the United States, and Vietnam [ 35 , 41 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…If greater percent of the household expenditure is utilized for FAFH, quality of foods consumed could be compromised [ 51 ]. These findings raise serious concern as the socioeconomic gradient in obesity is attributable to the setting or food environment that affects the poorer sections of the populations and identifies the need to study the effect of dietary behavior in such settings [ 52 , 53 ]. Work by Du and co-workers explained the combined effect of FAFH along with race, ethnicity, and low family income with all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these circumstances, it is imperative to analyse the growing trend of eating out from a nutritional standpoint, considering the mounting evidence linking consumption of out-of-home foods to issues such as excess body weight (7) , obesity (8) and increased risk of non-communicable diseases (6) . This alarming phenomenon is predominantly attributed to the high intake of fat, salt and calories in food (5,7) . The connection between excessive dietary salt intake and hypertension (9)(10)(11) has become increasingly apparent.…”
mentioning
confidence: 99%